Using WhatsApp to Increase Students’ Ability in English: Teacher’s Creativity - Daulay, Sholihatul Hamidah; Damanik, Emeliya Sukma Dara; Kiflaini (JET ADI BUANA, 2022)
During the Covid-19 pandemic, it is necessary for every educational institution to carry out online learning at home. To increase student achievement, the creativity of teachers in the online learning process is needed, especially in the use of the WhatsApp application. Teacher creativity is the competence possessed by teachers in teaching not only mastering the material, but a teacher must also be able to be innovative, creative and combine in the use of media, methods, strategies and a comfortable and unsaturated learning atmosphere. The purpose of this study is to find out how teacher’s creativity in using WhatsApp to increase students' ability in English and to know the inhibiting and supporting factors for teacher's creativity to increase students' Ability in English at grade 8-1 of MTs Parmiyatu Wassa'adah. The place of this research is at Madrasah Tsanawiyah Swasta Parmiyatu Wassa'adah. The data collected by the researcher are information that is in line and connected with the formulation of the research problem.  There are two sources of data obtained, namely primary data sources and secondary data sources. As for the details of the results of the study 1) the authors found that teachers in the field of English studies tried to be as creative as possible in every subject matter taught to improve students' English skills, this was proven by the use of all the features on the WhatsApp application. The features used are Voice notes, Audio/video calls, Text message, WhatsApp status, striker, Gif, photo and video. Each application used is adjusted to the needs of the subject matter. 2) The inhibiting faced by teachers in the field of English studies during learning using the WhatsApp application were caused by two factors, namely internal factors and external factors. 3) Supporting factors to overcome the barriers to creativity of English teachers in using WhatsApp through research, the authors found several supporting factors including providing sanctions, using audio features, video calls and documents, using WhatsApp features, registering students to get free quotas, tolerance, and establish communication with the families of students